Age-Related Risk Factors and Complications of Patients With COVID-19: A Population-Based Retrospective Study - Zhang, Han; Wu, Yingying; He, Yuqing; Liu, Xingyuan; Liu, Mingqian; Tang, Yuhong; Li, Xiaohua; Yang, Guang; Liang, Gang; Xu, Shabei; Wang, Minghuan; Wang, Wei (Frontiers in Medicine, 2022)
Objective: To study the differences in clinical characteristics, risk factors and complications across age-groups among COVID-19 inpatients. Methods: In this population-based retrospective study, we included all the COVID-19 positive hospitalized patients at Wuhan City from Dec 29, 2019 to April 15, 2020 during the first pandemic wave. Multivariate logistic regression analyses were used to explore risk factors for death from COVID-19. Canonical correlation analysis was performed to study the associations between comorbidities and complications. Results: There are 36,358 patients in the final cohort, of whom 2492 (6.85%) died. Greater age (OR=1.061 [95%CI 1.057-1.065], p<0.001), male gender (OR=1.726 [95%CI 1.582-1.885], p<0.001), alcohol consumption (OR=1.558 [95%CI 1.355-1.786], p<0.001), smoking (OR=1.326 [95%CI 1.055-1.652], p=0.014), hypertension (OR=1.175 [95%CI 1.067-1.293], p=0.001), diabetes (OR=1.258 [95%CI 1.118-1.413], p<0.001), cancer (OR=1.86 [95%CI 1.507-2.279], p<0.001), chronic kidney disease (CKD) (OR=1.745 [95%CI 1.427-2.12], p<0.001), and intracerebral hemorrhage (OR=1.96 [95%CI 1.323-2.846], p=0.001) were independent risk factors for death from COVID-19. Patients aged 40-80 years had similar risk factors to the whole patients. For patients aged <40 years, only cancer (OR=17.112 [95%CI 6.264-39.73], p<0.001) and ICH (OR=31.538 [95%CI 5.213-158.787], p<0.001) were significantly associated with higher odds of death. For patients aged >80 years, only age (OR=1.033[95%CI 1.008-1.059], p=0.01) and male gender (OR=1.585 [95%CI 1.301-1.933], p<0.001) were associated with higher odds of death. The incidence of most complications increases with age, but arrhythmias, gastrointestinal bleeding, and sepsis were more common in younger deceased COVID-19 patients, with only arrhythmia reaching statistical difference (p=0.039). We found a relatively poor correlation between preexisting risk factors and complications. Conclusions: COVID-19 are disproportionally affected by age for its clinical manifestations, risk factors, complications, and outcomes. Prior complications has little affect on the incidence of extrapulmonary complications.